Dapagliflozin once‐daily and exenatide once‐weekly dual therapy: A 24‐week randomized, placebo‐controlled, phase II study examining effects on body weight and prediabetes in obese adults without diabetes. Issue 1 (26th September 2016) - Lundkvist, Per; Sjöström, C. David; Amini, Sam; Pereira, Maria J.; Johnsson, Eva; Eriksson, Jan W.
Abstract : Aims: To explore the effects of dual therapy with dapagliflozin and exenatide on body weight, body composition, glycaemic variables and systolic blood pressure (SBP) in obese adults without diabetes. Materials and methods: In this single‐centre, double‐blind trial, we randomized 50 obese adults without diabetes (aged 18–70 years; body mass index 30–45 kg/m 2 ) to oral dapagliflozin 10 mg once daily plus subcutaneous long‐acting exenatide 2 mg once weekly or placebo. MRI was used to assess change in body composition. Participants were instructed to follow a balanced diet and exercise moderately. Results: Of 25 dapagliflozin/exenatide‐ and 25 placebo‐treated participants, 23 (92.0%) and 20 (80.0%) completed 24 weeks of treatment, respectively. At baseline, the mean participant age was 52 years, 61% were female, the mean body weight was 104.6 kg, and 73.5% of participants had prediabetes (impaired fasting glucose or impaired glucose tolerance). After 24 weeks, for dapagliflozin/exenatide versus placebo: the difference in body weight change was −4.13 kg (95% confidence interval −6.44, −1.81; P < .001), which was mostly attributable to adipose tissue reduction without lean tissue change; 36.0% versus 4.2% of participants achieved ≥5% body weight loss, respectively; and prediabetes was less frequent with active treatment (34.8% vs 85.0%, respectively; P < .01). The difference in SBP change for dapagliflozin/exenatide versus placebo was −6.7 mm Hg. As expected, nausea and injection‐site reactions were more frequent with dapagliflozin/exenatide than with placebo. Only two and three participants, respectively, discontinued because of adverse events. Conclusions: Compared with placebo, dapagliflozin/exenatide dual therapy reduced body weight, frequency of prediabetes and SBP over 24 weeks and was well tolerated in obese adults without diabetes.